The role of Maritime Training in Algeria in achieving the Sustainable Development Goals - Lydia Djennadi; Wissam Belimane; Linda Gardelle (Dirassat Journal Economic Issue, 2025)
Algeria has officially adopted the United Nations' 2030 Agenda and is committed to achieving the 17 Sustainable Development Goals (SDGs), including SDG 14, "Life Below Water," which concerns the maritime sector, a strategic component of the national economy. In this regard, several measures have been implemented, notably the training of maritime professionals to reduce accidents affecting the marine environment and contribute to addressing maritime challenges. This paper aims to examine the regulatory frameworks and policy orientations governing this field and to evaluate the nature and content of maritime training programs in order to determine their role in advancing the SDGs. Data were collected through a qualitative approach combining document analysis and interviews. The findings reveal that Algeria has established strategic orientations for the maritime sector to address environmental challenges and mitigate the stagnation observed in SDG 14 progress. A legislative and institutional framework has been developed, and maritime training and research have been integrated into the strategies of higher education institutions. Regarding training programs, ENSM designs and offers degree, qualification, and certification programs to meet the sector’s needs. However, the study highlights a lack of international partnerships and the limited presence of social sciences and humanities courses in maritime training curricula. As for sustainable development concepts, the results show that they are integrated into certain modules of training programs, in addition to other seminars and study days organized to raise awareness of these issues.